PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL (STUDI DI PERUSAHAAN DAERAH PASAR KOTA DENPASAR) - Sari, Ade Yunita; Supartha, W G; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.01.TAHUN 2017, 2016)
This study aimed to examine the effect of Transformational Leadership on Job Satisfaction and Organizational Commitment. The research have conducted on employees of Perusahaan Daerah Pasar Kota Denpasar. The total sample of 169 employees, the data was collected using a questionnaire. Furthermore, the data were analyzed using Partial Least Square (PLS) with the support of SMARTPLS 2.0 software. The results of this study concluded that transformational leadership has a positive and significant effect on job satisfaction, transformational leadership has a positive and significant  effect on organizational commitment and job satisfaction is a significant positive effect on organizational commitment. The findings indicate that the influence of transformational leadership on organizational commitment is indirect, mediated by job satisfaction. Managerial implications of this research on human resource strategy to pay more attention to employee’s satisfaction with improve the implementation of transformational leadership to increase organizational commitment of employee’s in Perusahaan Daerah Pasar Kota Denpasar.
Keywords: Transformational Leadership, Job Satisfaction and Organizational Commitment.